2019
DOI: 10.5812/modernc.92471
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Mothers’ Concerns and Nursing Support of Children Admitted to Baqiyatallah Al-Azam Hospital of Ali Abad Katoul, Golestan Province, Iran, in 2018

Abstract: Background: Hospitalization of children is one of the main causes of anxiety and concern for families. Mothers of sick children need emotional support to provide effective care and adequate support for their children. Objectives: Thus, the present study was conducted to investigate the relationship between parental concerns and nursing support of hospitalized children. Methods: This descriptive cross-sectional study was conducted on 150 mothers of children admitted to the Pediatric Ward of Baqiyatallah Al-Azam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
2
4
1
Order By: Relevance
“…This result inconsistent with the study of Sanjari et al ( 2009) [22].The monthly family income of the participants was 14723.21(SD=7802.99) Taka which was similar to the national standard in Bangladesh, According to Trading Economics global macro models and analysts expectations in Bangladesh is expected to reach 15100.00 BDT/Month by the end of 2020. The result was incongruent with the study conducted in other countries, found that most of the participants family income was insufficient [21,23].…”
Section: Mothers and Childs Characteristicscontrasting
confidence: 88%
“…This result inconsistent with the study of Sanjari et al ( 2009) [22].The monthly family income of the participants was 14723.21(SD=7802.99) Taka which was similar to the national standard in Bangladesh, According to Trading Economics global macro models and analysts expectations in Bangladesh is expected to reach 15100.00 BDT/Month by the end of 2020. The result was incongruent with the study conducted in other countries, found that most of the participants family income was insufficient [21,23].…”
Section: Mothers and Childs Characteristicscontrasting
confidence: 88%
“…The scale's total score ranges from 0 to 30, with higher scores indicating higher levels of parental concerns. Factor analysis revealed five major groups of stressors, including environmental adjustment (0 to 8), lack of staff communication programs (0 to 4), hospital costs (0 to 2), loss of independence (0 to 2), and lack of information (0 to 4) (24).…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire includes 4 items for measuring factor thinking, 4 items for measuring strategic thinking, and 4 deviant items, and its scoring method is based on a five-option Likert's scale from completely disagree (score 1) to completely agree (score 5). The subscale of factor thinking includes four questions (2,9,12,10), the subscale of strategic thinking has four questions (1,4,7,8) and the other 4 questions (3,5,6,11) are considered deviant questions [16]. Snyder et al [15] determined the internal consistency of the whole scale be between 0.74 and 0.84 through Cronbach's alpha.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, hopeful people are less distressed and more adaptive to the diagnosis and treatment of cancer [1]. However, this requires learning new skills and training or using new methods that are beyond the patient's control, and therefore, they require the support of others, including psychotherapists [6,7]. Moreover, supportive care with different counseling methods is an integral part of patient treatment [8].…”
Section: Introductionmentioning
confidence: 99%